Pelatihan Pembuatan Handsanitizer di Desa Karangrau, Kecamatan Sokaraja, Banyumas Sebagai Program KKN Tematik Covid-19 - Afifah Dian Safitri; Rima Oktavia Kusuma; Rudy Wijaya; Muh. Sulaiman Dadiono (PT. Gyandharma Global Media, 2025)
Hand sanitizer is one of the preventive efforts in tackling the spread of Covid-19, As a form of intervention, training on making independent hand sanitizers has been carried out for the people of Karangrau Village, Banyumas to increase its availability and accessibility. This activity was carried out through direct assistance and survey methods. The results of the training showed an increase in public awareness of the importance of using hand sanitizers and the ease of obtaining these products independently.